You need to solve for x and y the system of simultaneous equations, hence you should use the second equation to write y in terms of x such that:

`y = x - 4`

You need to substitute `x - 4` for x in equation `9x^2+4y^2=36` such that:

`9x^2 + 4(x - 4)^2=36 `

Expanding the binomial yields:

`9x^2 + 4x^2 - 32x + 64 - 36 = 0`

`13x^2 - 32x + 28 = 0`

You should use quadratic formula to find x such that:

`x_(1,2) = (32 +- sqrt(1024 - 1456))/26`

`x_(1,2) = (32 +- i*sqrt 432)/26`

`x_(1,2) = (32 +- 12i*sqrt3)/26`

`x_(1,2) = (16 +- 6i*sqrt3)/13`

`y_(1,2) =(16 +- 6i*sqrt3)/13 - 4`

`y_(1,2) = (36 +- 6i*sqrt3)/13 `

**Hence, evaluating the complex solutions to the system yields `x_(1,2) = (16 +- 6i*sqrt3)/13 and y_(1,2) = (36 +- 6i*sqrt3)/13.` **